Dysmenorrhea in Chronic Spontaneous Urticaria: A Subset of Patients Report Worsening and Partial Antihistamine Benefit: UCARE HURDLE-I Study - TÜRK M.; Yücel M. B.; YILMAZ İ.; Ertaş R.; ŞAHİNER Ü. M.; Demir S.; Gelincik A.; Ünal D.; Çelik Kamacı Ş.; Hörmet İğde M.; et al. (My University, 2026)
Background: Histamine plays a central role in CSU pathogenesis and may contribute to extracutaneous symptoms such as dysmenorrhea, but this relationship has not been fully examined. Methods: In this prospective, cross-sectional multicenter study, 425 female CSU patients and 370 age-matched controls were recruited from 19 UCARE centers in Türkiye. Dysmenorrhea prevalence and severity were assessed using a numerical scale and symptom scores. Histamine skin prick testing (SPT) was performed to evaluate histamine clearance capacity. Associations between dysmenorrhea, CSU phenotype, antihistamine use, and SPT kinetics were analyzed. Results: The prevalence and severity of dysmenorrhea were comparable between CSU patients and controls (81.6% vs. 79.5%, p = 0.244). However, 95/418 (22.7%) of CSU patients reported increased menstrual pain following CSU onset, and 20/95 (21.1%) of these reported partial relief with antihistamines. CSU patients with worsened dysmenorrhea exhibited significantly shorter histamine SPT positivity durations than those without symptom change (35 vs. 45 min; p = 0.015). No correlation was observed between dysmenorrhea severity and total IgE, anti-TPO levels, or urticaria control/activity scores. A moderate negative correlation was found between UAS7 and elapsed time to histamine SPT negativity (r = −0.389, p < 0.001). Conclusions: Although overall prevalence and severity of dysmenorrhea were similar in CSU patients and healthy controls, about one in five patients with CSU experienced worsening menstrual pain after disease onset, and only a subset of these patients reported partial improvement with antihistamines. A distinct CSU subgroup with heightened menstrual pain may be characterized by altered histamine dynamics. Whether these patients may benefit from more intensive antihistamine treatment remains uncertain and requires confirmation in future studies; further studies should explore neuroimmune and hormonal mechanisms underlying this overlap.
Keywords: Tıp; Dahili Tıp Bilimleri; Dermatoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Dermatology; Health Sciences; Klinik Tıp (Med); Klinik Tıp; Clinical Medicine (Med); Clinical Medicine; chronic spontaneous urticaria; dysmenorrhea; histamine; skin prick test